Gene Status in HER2 Equivocal Breast Carcinomas: Impact of Distinct Recommendations and Contribution of a Polymerase Chain Reaction‐Based Method. (16th October 2014) - Sapino, Anna; Maletta, Francesca; Verdun di Cantogno, Ludovica; Macrì, Luigia; Botta, Cristina; Gugliotta, Patrizia; Scalzo, Maria Stella; Annaratone, Laura; Balmativola, Davide; Pietribiasi, Francesca; Bernardi, Paolo; Arisio, Riccardo; et al.
Abstract : Background: The primary objectives of this study on carcinomas with equivocal HER2 expression were to assess the impact of distinct recommendations with regard to identifying patients eligible for anti‐HER2 agents by fluorescence in situ hybridization (FISH) and to elucidate whether multiplex ligation‐dependent probe amplification (MLPA) may be of support in assessing HER2 gene status. Methods: A cohort of 957 immunohistochemistry‐evaluated HER2‐equivocal cases was analyzed by dual‐color FISH. The results were assessed according to U.S. Food and Drug Administration (FDA) and European Medicines Agency (EMA) guidelines and American Society of Clinical Oncology (ASCO) and College of American Pathologists (CAP) 2007 and 2013 guidelines for dual‐ and single‐signal in situ hybridization (ISH) assays. A subgroup of 112 cases was subjected to MLPA. Results: HER2 amplification varied from 15% (ASCO/CAP 2007 HER2 /CEP17 ratio) to 29.5% (FDA/EMA HER2 copy number). According to the ASCO/CAP 2013 interpretation of the dual‐signal HER2 assay, ISH‐positive carcinomas accounted for 19.7%. In contrast with the ASCO/CAP 2007 ratio, this approach labeled as positive all 32 cases (3.34%) with a HER2 /CEP17 ratio <2 and an average HER2 copy number ≥6.0 signals per cell. In contrast, only one case showing a HER2 copy number <4 but a ratio ≥2 was diagnosed as positive. MLPA data correlated poorly with FISH results because of the presence of heterogeneous HER2 amplification in 33.9% of all amplified carcinomas; however, MLPA ruled out HER2 amplification in 75% of ISH‐evaluated HER2‐equivocal carcinomas. Conclusion: The ASCO/CAP 2013 guidelines seem to improve the identification of HER2‐positive carcinomas. Polymerase chain reaction‐based methods such as MLPA can be of help, provided that heterogeneous amplification has been ruled out by ISH. Abstract : The authors sought to assess the impact of recommendations with regard to identifying patients eligible for anti‐HER2 agents by fluorescence in situ hybridization and to elucidate whether multiplex ligation‐dependent probe amplification (MLPA) may be of help in assessing HER2 gene status. Recent guidelines seem to improve the identification of HER2‐positive carcinomas. MLPA can be of help if heterogeneous amplification has been ruled out.